Altered Intrinsic Properties and Inhibitory Connectivity in Aged Parvalbumin-Expressing Dorsal Horn Neurons - Gradwell, Mark A.; Smith, Kelly M.; Dayas, Christopher V.; Smith, Douglas W.; Hughes, David I.; Callister, Robert J.; Graham, Brett A. (Frontiers in Neural Circuits, 2022)
The incidence of pain symptoms such as allodynia are known to increase with age. Parvalbumin expressing interneurons (PVINs) within the dorsal horn (DH) of the spinal cord play an important role in allodynia whereby their inhibitory connections prevent innocuous touch information from exciting nociceptive pathways. Here we ask whether the functional properties of PVINs are altered by aging, comparing their functional properties in adult (3–7 month) and aged mice (23–28 month). Patch clamp recordings were made from PVINs in laminae IIi-III of parasagittal spinal cord slices. The intrinsic excitability of PVINs changed with age. Specifically, AP discharge shifted from initial bursting to tonic firing, and firing duration during current injection increased. The nature of excitatory synaptic input to PVINs also changed with age with larger but less frequent spontaneous excitatory currents occurring in aged mice, however, the net effect of these differences produced a similar level of overall excitatory drive. Inhibitory drive was also remarkably similar in adult and aged PVINs. Photostimulation of ChR2 expressing PVINs was used to study inhibitory connections between PVINs and unidentified DH neurons and other PVINs. Based on latency and jitter, monosynaptic PVIN to unidentified-cell and PVIN-PVIN connections were compared in adult and aged mice, showing that PVIN to unidentified-cell connection strength increased with age. Fitting single or double exponentials to the decay phase of IPSCs showed there was also a shift from mixed (glycinergic and GABAergic) to GABAergic inhibitory transmission in aged animals. Overall, our data suggest the properties of PVIN neurons in aged animals enhance their output in spinal circuits in a manner that would blunt allodynia and help maintain normal sensory experience during aging.